PELATIHAN PENGEMBANGAN KETERAMPILAN SISWA DI SMKN 1 BINTAN UTARA, KABUPATEN BINTAN - Hardini, Widi; Cherryline, Violetta; Abnur, Asman; Budhiartha, I Nyoman; Lapotulo, Nensi; Saputra, Eryd; Simangunsong, Estheria Morhencie (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Community service (PKM) is one form of real contribution from higher education in improving Indonesia's education quality. This activity aims to develop students' skills at SMKN 1 North Bintan, Bintan Regency, through structured and needs-based training. The methods used include lectures, discussions, and direct practice. The evaluation results showed an increase in student skills by 30% based on pre-test and post-test data. This article comprehensively discusses the implementation of this PKM, including its implications and potential for development